A Novel Temperature-Insensitive Hydrostatic Liquid-Level Sensor Using Chirped FBG - Vorathin, E.; Hafizi, Z.M.; Aizzuddin, A.M.; Zaini, Muhammad Khairol Annuar; Lim, Kok Sing (Institute of Electrical and Electronics Engineers (IEEE), 2019)
A novel half-bonded chirped fiber Bragg grating on a natural rubber diaphragm has been proposed to enhance the sensitivity and to compensate the temperature effects of a hydrostatic liquid-level sensor. This innovative fabrication method is resulted in the narrowing of the bandwidth with the hydrostatic pressure sensitivity recorded at-253 pm/kPa and water column sensitivity at-0.0253 nm/cm. The bandwidth modulation measurement was insensitive to temperature variations when compared with center wavelength modulation measurement. Furthermore, the proposed hydrostatic liquid-level sensor is compatible with a low-cost photodetector.